KORELASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF-CONFIDENCE MELALUI MODEL DISCOVERY LEARNING BERBANTUAN QUIZIZZ - shabira fitrah amalia (Euclid, 2025)
This study aims to find out whether there is a positive correlation between mathematical problem solving skills and student self-confidence through the Discovery Learning model assisted by Quizizz. The research method used is a quasi-experiment with a non-equivalent control group design. The problem solving ability test is 5 questions and a questionnaire with 32 questions related to student self-confidence. Data analysis using IBM SPSS 27 for Windows. The objects in this study are problem solving ability and self-confidence. The sampling technique used in this study was purposive sampling technique. Class X-2 as the experimental class was given the Discovery Learning model treatment assisted by Quizizz, while class X-4 as the control class which was given the usual learning model, namely PBL. The number of samples for each class was 27 students. The results of this study indicate that there is a correlation between problem solving ability and self-confidence with the use of the Discovery Learning model assisted by Quizizz which is 0.761, including a strong and positive category.